Exploration of exciton dynamics in GaTe nanoflakes via temperature- and power-dependent time-resolved photoluminescence spectra - Yan, Hongyan; Liang, Xilong; Dong, Shuai; Lei, Yu; Zhang, Guofeng; Chen, Ruiyun; Hu, Jianyong; Jing, Mingyong; Wang, Shen; Su, Xingliang; Qin, Chengbing; Xiao, Liantuan; et al. (Optics express, 2021)
GaTe nanoflakes have been receiving much research attention recently due to their applications in optoelectronic devices, such as anisotropic non-volatile memory, solar cells, and high-sensitivity photodetectors from the ultraviolet to the visible region. Further applications, however, have been impeded due to the limited understanding of their exciton dynamics. In this work we perform temperature- and power-dependent time-resolved photoluminescence (PL) spectra to comprehensively investigate the exciton dynamics of GaTe nanoflakes. Temperature-dependent PL measurements manifest that spectral profiles of GaTe nanoflakes change dramatically from cryogenic to room temperature, where the bound exciton and donor-to-acceptor pair transition normally disappear above 100 K, while the charged exciton survives to room temperature. The lifetimes of these excitons and their evolution vs temperature have been uncovered by time-resolved PL spectra. Further measurements reveal the entirely different power-dependent exciton behaviors of GaTe nanoflakes between room and cryogenic temperatures. The underlying mechanisms have been proposed to explore the sophisticated exciton dynamics within GaTe nanoflakes. Our results offer a more thorough understanding of the exciton dynamics of GaTe nanoflakes, enabling further progress in engineering GaTe-based applications, such as photodetectors, light-emitting diodes, and nanoelectronics.